Regional choreographic schools in Ukraine: the socio-cultural and pedagogical aspects - Ostroverkh, Tetiana; Pavliuk, Tetiana; Degtiar, Daria; Myroniuk, Nataliia; Korytna, Alina; Boichenko, Olena (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
It is very important to preserve and develop folk choreographic culture in the modern socio-cultural space research of regional dance traditions. This is especially true for those territories, which are now only fragmentarily represented in Ukrainian art history. The aim of this study was to identify the main trends and establish the peculiarities of socio-cultural and pedagogical aspects of regional dance schools in Ukraine. This cross-sectional study was carried out on a sample of 264 scientific and pedagogical employees engaged in scientific and teaching activities in the field of choreography at higher education institutions in Ukraine, namely Kyiv University of Culture, Kyiv National University of Culture and Arts (KNUCA), Volyn National University named after Lesya Ukrainka, and Kyiv Municipal Academy of Variety and Circus Arts. While writing this article, we also analyzed the works of international researchers. A questionnaire consisting of 4 questions was used for data collection and the analytical methods were descriptive statistics (percentage). According to the study results, the features of the formation of choreographic schools in different geographical and cultural regions of Ukraine highlight promising areas of their development from the perspective of scholars of choreography engaged in scientific and teaching activities in higher education institutions. In conclusion, Ukrainian regional choreography is a creative and multidimensional phenomenon. In each region of Ukraine, folk ethnography is characterized by its authentic features and way of performance due to geographical, historical, social, political, economic, and other factors.